Long-Term Outcomes of Patients Diagnosed With Sacral Chordoma in a Retrospective Multicenter Study - Aneta Maria Borkowska PhD; Andrzej Pieńkowski MD; Paulina Chmiel MD; Tomasz Skóra MD; Radosław Michalik PhD; Piotr Rutkowski Prof.; Mateusz Jacek Spałek PhD (Cancer Control)
Background Chordoma is a rare and aggressive primary bone sarcoma. En-block resection remains the primary treatment, but some patients are unable to undergo it due to the location and potential complications. Currently, there is no direct comparison of the effects of radiotherapy (RTH) and surgical treatment. However, retrospective analyses indicate the potential benefits of using RTH. Methods A retrospective analysis was conducted on 48 patients with sacral chordoma who were treated with surgery and/or radiotherapy between 2001-2020. Among those, 22 were initially treated with surgery, 19 with definitive radiotherapy, and 7 received combined treatment. The outcomes of the treatment of recurrence in 16 patients were considered. The resection margins were defined according to R classification, and the Kaplan-Meier method was employed to calculate disease-free survival (DFS) and overall survival (OS). Results The median (mOS) for the entire cohort was 80.6 months (95% CI: 62.3-NA), and the median (mDFS) was 40.4 months (95% CI: 35-69.5). Patients who underwent radical surgery of the primary tumor did not achieve the mOS (mean 68), while patients treated only with RTH for the primary tumor achieved an mOS of 62.3 months (95% CI: 52.1-NA). This resulted in a significant advantage of surgery over RTH in terms of OS ( P = 0.01). This was not observed for DFS. The 3-year DFS rates were 65% in the surgical treatment group and 53.3% in the RTH group. The 3-year OS rates were 96% in the surgery group and 88.9% in the RTH group. In the treatment of recurrence, there were no statistically significant differences between RTH and surgery, for OS ( P = 0.76). Conclusions Radical surgery remains the optimal treatment for sacral chordoma. For patients who are not candidates for surgical intervention, RTH offers excellent long-term outcomes. The treatment of recurrence remains a significant challenge. Comparing modern RTH techniques and surgical procedures could provide further insights.